1993
DOI: 10.3109/00365529309096095
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Glycoconjugates in Pancreatic, Gastric, and Colonic Tissue by Bauhinia purpurea, Vicia villosa, and Peanut Lectins

Abstract: We have earlier prepared a pancreatic cancer-associated mucin, whose altered carbohydrate structure was recognized by Vicia villosa (VVA), Bauhinia purpurea (BPA), and peanut (PNA) lectins and which was found preferentially in the sera of patients with pancreatic or gastric cancer. Cancer-associated structures of the sugar chain on serum antigen may reflect those occurring in malignant tissues. Accordingly, we investigated the tissue distribution of carbohydrate structures reactive to these lectins by using le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Additionally, we have previously shown that B. variegata lectin has pro-infl ammatory activity, inducing neutrophil migration dependent on resident mast cells (Alencar et al 2001). BVL is similar to B. purpurea agglutinin, which has been used to probe the structural and functional role of cell surface carbohydrates (Horan et al 1999), to detect sugar moieties on normal and neoplastic cell surfaces (Sarker et al 1994), to serve as a marker for identifi cation of different cell types and as a reagent for cell separations (Shue et al 1993;Kasper et al 1994;Sarker et al 1995). This observation suggests that BVL I and BVL II can also be used as potential tools for the study of several biological activities in different cellular systems.…”
Section: Characterization Of the Predicted Bvl Proteinmentioning
confidence: 99%
“…Additionally, we have previously shown that B. variegata lectin has pro-infl ammatory activity, inducing neutrophil migration dependent on resident mast cells (Alencar et al 2001). BVL is similar to B. purpurea agglutinin, which has been used to probe the structural and functional role of cell surface carbohydrates (Horan et al 1999), to detect sugar moieties on normal and neoplastic cell surfaces (Sarker et al 1994), to serve as a marker for identifi cation of different cell types and as a reagent for cell separations (Shue et al 1993;Kasper et al 1994;Sarker et al 1995). This observation suggests that BVL I and BVL II can also be used as potential tools for the study of several biological activities in different cellular systems.…”
Section: Characterization Of the Predicted Bvl Proteinmentioning
confidence: 99%
“…A chimeric lectin recombinantly produced from BPA and Lens culinaris showed a different binding affinity than its original parental ones (Yamamoto et al, 2000b). Because of the different affinity of BPA to the surface, as well as cytoplasmic glycan distribution in various cell types described previously (Kasper et al, 1994;Sarker et al, 1992Sarker et al, , 1994Sarker et al, , 1995Shue et al, 1993), we were impelled to examine its binding characteristics. Although the structural nature required for BPA binding with carbohydrates has been documented via quantitative precipitin (QPA) and precipitin inhibition assays (QPIA) (Wu et al, 1980), this information is mainly limited to monomer or submolecular Galh1-3GalNAc (T) and Galh1-related oligosaccharides.…”
Section: Introductionmentioning
confidence: 97%
“…It is a glycoprotein (gp) containing a long metal-binding loop, part of which determines its carbohydrate specificity (Yamamoto et al, 2000a). The specific binding properties of BPA have been applied to probe the structural and functional role of cell surface carbohydrates (Horan et al, 1999), to detect sugar moieties on normal and neoplastic cell surfaces (Sarker et al, 1994), to serve as a marker for identification of different cell types, and as a reagent for cell separations (Kasper et al, 1994;Sarker et al, 1992Sarker et al, , 1995Shue et al, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…Because these cancer cell lines are heterogeneous, it is inadequate to define the NEC lectins as merely not binding to these gastric cancer cell lines. In fact, both PNA and VVA are NEC lectins expressed in primary AGC, and moreover it was reported that these lectins bind to gastric cancer cells [34][35][36]. This designation should therefore limit this analysis.…”
Section: Discussionmentioning
confidence: 99%